Taxonomic Profile of Cultivable Microbiota from Adult Sheep Follicular Fluid and Its Effects on In Vitro Development of Prepubertal Lamb Oocytes - Mrenoshki, Slavcho; Temerario, Letizia; Mastrorocco, Antonella; Visci, Grazia; Notario, Elisabetta; Marzano, Marinella; Martino, Nicola Antonio; Mrenoshki, Daniela; Lacalandra, Giovanni Michele; Pesole, Graziano; Dell’Aquila, Maria Elena (Animals (Basel), 2025)
The aims of the present study were to analyze the taxonomic profile and to evaluate the functional effects of sheep FF cultivable microbiota on prepubertal lamb oocytes PLOs developmental potential. Ovarian FFs were recovered from slaughtered adult sheep via the aspiration of developing follicles and used for microbiota propagation. Bacterial pellets underwent 16S rRNA gene sequencing and targeted culturomics, whereas cell-free supernatants were used as supplements for the in vitro maturation (IVM) of slaughtered PLOs. For the first time, bacteria presence in adult sheep FF was detected, with the first report of Streptococcus infantarius subsp. infantarius (as a species) and Burkholderia cepacia (as a genus and species) in either animal or human FF. The short- and long-term effects of bacterial metabolites on PLO maturation and embryonic development were demonstrated. As short-term effects, the addition of FF microbiota metabolites did not affect the oocyte nuclear maturation and mitochondria distribution pattern, except in one of the examined supernatants, which reduced all quantitative bioenergetic/oxidative parameters. As long-term effects, one of them reduced the total cleavage rate after in vitro embryo culture (IVC). In conclusion, microbiota/bacteria are present in adult sheep FF and may influence reproductive outcomes in vitro. Future studies may reveal the beneficial in vitro effects using the microbiome from preovulatory follicles.